Influence of sintering temperature on microstructure and mechanical properties of graphene-reinforced Inconel 738 LC composites. (2021) - Ogunbiyi, Olugbenga; Salifu, Smith; Sadiku, Rotimi; Jamiru, Tamba; Adesina, Oluwagbenga; Adesina, Olanrewaju Seun
Abstract: Graphene/Inconel 738LC composites were synthesized using spark plasma sintering technique and the microstructural features were investigated using Optical microscope, Scanning electron microscope and X-ray diffraction machine. The microhardness, porosity and fracture toughness of the graphene-reinforced Inconel 738LC matrix composites were obtained. The processing parameters used were sintering pressure of 40 MPa, heating rate of 100 °C/min, soaking time of 5 min and varied sintering temperatures between 1000 and 1100 °C. The results show that spark plasma sintering is a viable powder metallurgy technique to develop graphene-reinforced Inconel 738LC composite. The increase in sintering temperature shows that there was significant increase in the hardness property of the sintered composites while the porosity and fracture toughness significantly reduced. Intermetallic and solid solution phases were formed within the microstructure which enhanced the strength of the sintered composites. In this study, the highest microhardness value (469 Hv), lowest porosity (1.47%) and fracture toughness value (26) was obtained in the composite sintered at 1100 °C.